Le fond plat, avenir prometteur de l’aérostation - Béesau, Christophe (Comptes Rendus. Mécanique)
Innovative aerostat projects have proliferated in recent years, fueled by the rising cost of kerosene, but also because “conventional” air transport has become one of the culprits of global warming. The “lighter-than-air” is indeed economical by nature, since it only uses energy to move, not to stay aloft. But landing instability remains a historical weakness of airships. However, a patent modifying the profile of the aircraft’s bottom provides a solution to this problem that is as elegant as it is effective, and changes the game by giving the aircraft outstanding aerodynamic properties.